BEBERAPA PENANDA (MARKER) PADA EARLY CHILDHOOD CARIES (ECC) DAN SAVERE EARLY CHILDHOOD CARIES (S-ECC): (SUATU TINJAUAN IMUNOLOGIS) - Eko Sri Yuni Astuti (Interdental: Jurnal Kedokteran Gigi, 2020)
Early childhood caries (ECC) is caries that affects children under the age of 6. According to the American Academy of Pediatric Dentistry (AAPD), ECC is defined as the presence of one or more teeth with caries (cavities or no cavities), missing teeth due to caries or the presence of restoration deciduous teeth in children under 71 months. If it occurred on the smooth surface of the tooth in children under 3 years of age, indicating severe early childhood caries (S-ECC). Streptococcus Mutans plays a role in the etiology of caries of preschool children, which is a contagious infectious disease, Streptococcus Mutans are acidogenic bacteria (can produce acid) and aciduric (can live in acidic environments). The occurrence of caries is a complex process of interaction between host factors (teeth), microorganisms, substrates (carbohydrates) and the environment, including saliva. Several markers related to ECC and S-ECC namely lysozyme, lactoferrin saliva, IL-8, CD36 salivary neutrophil.